2000
DOI: 10.1007/s007870070032
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a child-specific cross-cultural instrument for assessing posttraumatic stress disorder

Abstract: The Posttraumatic Stress Symptoms in Children (PTSS-C) was developed as a cross-cultural semi-structured interview to diagnose posttraumatic stress disorder (PTSD) and to identify PTSD-non-related posttraumatic stress symptoms in children after various traumatic experiences. The psychometric properties were studied in two different child populations in Iraqi Kurdistan (the survivors of the military operation "Anfal", and the orphans), in a sample of Kurdistanian refugee children in Sweden, and in a comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…The PTSD prevalence of 32.3% in children in Kurdistan and 11.0% in the Kurdistanian children in Sweden is similar to the results of our previous studies (6,8,11). The results of this study provide some insight about the characteristics of childhood trauma and associated psychopathology among children of Kurdistanian background.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The PTSD prevalence of 32.3% in children in Kurdistan and 11.0% in the Kurdistanian children in Sweden is similar to the results of our previous studies (6,8,11). The results of this study provide some insight about the characteristics of childhood trauma and associated psychopathology among children of Kurdistanian background.…”
Section: Discussionsupporting
confidence: 91%
“…The psychometric properties of the PTSS-C have been assessed in previous research (11). The PTSS-C instrument yielded satisfactory internal consistency, high interrater reliability and excellent validity on crossvalidation with the Child Posttraumatic Stress Disorder Reaction Index (CPTSD-RI) (12), and the Diagnostic Interview for Children and Adolescents (DICA) according to the DSM-IV (13).…”
Section: Posttraumatic Stress Symptoms For Children (Ptss-c)mentioning
confidence: 97%
“…Other studies have also found significant, but rather unspecific, relationships between exposure to organized violence and PTSD-specific symptomatology (44)(45)(46). The three-factor PTSD model was confirmed in a study testing the validity of the ÔReaction of Adolescents to Traumatic Stress QuestionnaireÕ (RATS) in four populations of adolescents, but the scale also correlated highly with non-PTSD specific symptoms of anxiety and depression (47).…”
Section: Mental Health In Young Refugeesmentioning
confidence: 80%
“…The trained co-leader simultaneously uses the Crisis Screening Instrument to identify children showing any sign or symptom of psychological distress that is qualifying to further individual assessment. This instrument is derived from two widely used screening questionnaires with satisfactory validity and reliability in Kurdistan society [30,31]; Children showing positive screening are to be referred for individual assessment by a trained expert in using a Modified Family Map to identify risk and protecting factors in three generations in addition to examination of psychiatric status for planning of adequate management [32]. The CIPCA is hypothyzed to act as psychological vaccination against development of posttraumatic psychopathology [18,19].…”
Section: Crisis Intervention Program For Children and Adolescents (Cimentioning
confidence: 99%